KEKAYAAN INTELEKTUAL KOMUNAL DALAM PERSPEKTIF UU HAK CIPTA - Bagus Gede Ari Rama; Dewa Krisna Prasada; Kadek Julia Mahadewi (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2023)
Indonesia actually has enormous potential related to communal IP, considering that Indonesia consists of various tribes, customs and cultures as well as various other forms of local wisdom. This legal research aims to analyze the legal certainty of communal intellectual property in Indonesia. This legal research uses normative legal research methods and uses a statutory approach. The purpose of this research is to understand the types of communal IP in Indonesia and the arrangements for communal IP in the Copyright Law. This research found that there are 4 (four) types of communal intellectual property recognized in Indonesia, and communal intellectual property has been regulated in the Copyright Law in Article 38 and in Government Regulation Number 56 of 2022 concerning Communal Intellectual Property.